2020
DOI: 10.1007/s12011-020-02341-2
|View full text |Cite
|
Sign up to set email alerts
|

The Joint Role of Iodine Status and Thyroid Function on Risk for Preeclampsia in Finnish Women: a Population-Based Nested Case-Control Study

Abstract: Preeclampsia, a pregnancy disorder that includes hypertension and proteinuria, is a major cause of maternal and fetal morbidity and mortality. Some studies, but not all, have found that women with preeclampsia have significantly lower iodine levels than healthy pregnant women. Resolving this issue is important because iodine deficiency in pregnancy is common in the USA and parts of Europe including Finland. We conducted a nested case-control study to determine whether the risk for preeclampsia is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…A study by Reische et al [22], however, showed no significant difference in iodine levels (case mean = 26.04 ng/ mL, control mean = 27.88 ng/mL, p=0.995) between preeclamptic and healthy women. There was also no significant difference in the TSH levels between compared groups (case mean = 1.30 mIU/L, control mean = 1.24 mIU/L, p=0.896).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A study by Reische et al [22], however, showed no significant difference in iodine levels (case mean = 26.04 ng/ mL, control mean = 27.88 ng/mL, p=0.995) between preeclamptic and healthy women. There was also no significant difference in the TSH levels between compared groups (case mean = 1.30 mIU/L, control mean = 1.24 mIU/L, p=0.896).…”
Section: Discussionmentioning
confidence: 86%
“…There are many controversial results in the literature regarding the relationship between UIC and the risk of PE. Some of the studies reported lower iodine levels in women with PE compared to healthy pregnant women [19][20][21], while other studies show opposite results [9,22]. Iodine deficiency is very common among pregnant women in many European countries, as well as in the USA [23], therefore it is necessary to verify the possible relationship between the iodine level and the risk of PE.…”
Section: Article Infomentioning
confidence: 99%
“…The study was, however, limited by the very few numbers of included studies and high heterogeneity across studies. Reische et al [ 33 ] in a recent case-control study using nationally representative data from Finland reported no difference in serum iodine, TSH and other thyroid parameters of preeclamptic and normotensive pregnant women. Differences in the findings between these studies and ours could partly be accounted for by the timing of the iodine and thyroid function tests.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the findings between these studies and ours could partly be accounted for by the timing of the iodine and thyroid function tests. While the iodine and thyroid function status in our study were measured in the third trimester, the cohort studies in the systematic review [ 32 ], as well as the study by Richie et al [ 33 ], estimated the risk of preeclampsia based only on the iodine and thyroid function status estimates in the first trimester. This approach did not consider the impact of the iodine nutritional state in the second half of pregnancy on the risk of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…[9] . However, a nested case-control study showed no signi cant correlation between TSH levels and preeclampsia [10] . In addition, hypothyroidism and hypothyroxinemia were not linked to hypertensive disorders, but hyperthyroidism was linked to a higher chance of developing hypertension [11] .…”
Section: Introductionmentioning
confidence: 91%